Decreasing the carbon footprint of food through public procurement—A case study from the municipality of Härnösand - Kjellberg, Mari; Skoglund, Wilhelm; Haller, Henrik (Frontiers in Nutrition, 2024)
Eating habits are among the strongest drivers of negative environmental impact. Public procurement has been suggested as an efficient lever to catalyze changes within the food system. This study examines alternative purchase processes that may decrease the carbon footprint of the publicly procured food through a case study of a municipality in the Northern part of Sweden. The GHG emissions associated with the current food service in the case study were 2,2 kg CO2e per kg food and must be reduced by 40,9% by 2030, to comply with the Paris agreement. 76% of the emissions derive from food of animal origin (44% from unprocessed red meat). Three alternative diet scenarios; "Zero red meat", "50% red meat", "flexitarian free from red meat" were explored. Only 6% of the total purchased food kg were altered and yet the cutback of meat caused GHG emissions reductions turned out to be as high as 44%. The Swedish Law on Public Procurement, deficient infrastructure, unsustainable food culture, and local politicians reluctant to change were mentioned as the main obstacles for necessary changes in the food procurement system to materialize. The respondents also pointed out necessary policy changes on national as well as municipal level.